2014
DOI: 10.1186/1746-160x-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption, treatment time and extraction rate during orthodontic treatment with self-ligating and conventional brackets

Abstract: IntroductionThis study determined the amount and severity of EARR (external apical root resorption) after orthodontic treatment with self-ligating (SL) and conventional (Non-SL) brackets. Differences regarding rate of extraction cases, appointments and treatment time were evaluated.Material and methods213 patients with a mean age of 12.4 ± 2.2 years were evaluated retrospectively. The treatments were performed with SL brackets (n = 139, Smartclip, 3 M Unitek, USA) or Non-SL brackets (n = 74, Victory Series, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
0
26
2
2
Order By: Relevance
“…The full-texts of the reserved ten studies were retrieved and assessed referring to the inclusion and exclusion criteria. Finally, seven studies [1723] fulfilled the criteria and were included in present systematic review, five of which [1721] were pooled for meta-analysis. A flow diagram of the study selection process was demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The full-texts of the reserved ten studies were retrieved and assessed referring to the inclusion and exclusion criteria. Finally, seven studies [1723] fulfilled the criteria and were included in present systematic review, five of which [1721] were pooled for meta-analysis. A flow diagram of the study selection process was demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While some authors have reported significantly reduced treatment times for self-ligating brackets compared to conventional appliances [4], with a mean reduction of up to 4 months in treatment time (from 23.5 to 19.4 months; [5]), a majority of authors [6, 7, 21] have reported that self-ligating brackets are no more efficient than conventional ligated brackets in terms of tooth alignment, or that they are even inferior [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Porém, alguns estudos 12,13 demonstraram não haver diferença significativa entre os AL e BC. Um estudo revelou que não ocorre diferença estatística na quantidade de reabsorção radicular apical externa (RRAE) entre os AL e BC e que os incisivos centrais inferiores foram os dentes mais afetados 12 .…”
Section: Reabsorção Radicularunclassified
“…Um estudo revelou que não ocorre diferença estatística na quantidade de reabsorção radicular apical externa (RRAE) entre os AL e BC e que os incisivos centrais inferiores foram os dentes mais afetados 12 . Outro estudo revelou que também não houve diferença significativa na reabsorção radicular entre os AL e BC para os casos de apinhamento severo anterior 13 .…”
Section: Reabsorção Radicularunclassified